Źródła polonofilstwa Konstantego Balmonta (na materiale powieści autobiograficznej Pod nowym księżycem) - Olga Cybienko (Postscriptum Polonistyczne)
K. Balmont the representative of Russian symbolism had closer and deeper ties with the literature and culture of Poland, than other poets of the Russian “Silver age”. He was filled with Polishness. He had the talent to change himself completely, he could feel spiritual kinship with Polish people. He did much to create an attractive image of it in the eyes of Russian readers. Balmont translated his contemporaries – J. Kasprowicz, B. Leśmian, M. Jastrun, S. Wyspiański. He had always admired Polish romantics. He included fragment of their works into his essays with his own comments. It became a great event, when a collection of three dramatic plays by J. J. Słowacki “Balladyna”, “Lilla Veneda”, “HelionEolion” (a fragment from “Samuel Zborowski”) came out in the poetic translation of Balmont. The Russian poet had often glorified in his verse and lyrical prose the Polish speech, the Polish heart, the musical genius of Chopin, the great and heroic poetry of Polish exiles that revealed the tragic fate of the enslaved Poland. Balmont’s enthusiasm about Polish culture easily infected other Russian poets – A. Bely, A. Blok.